Hillslope and Watershed Hydrology - Christopher J. Duffy (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Watershed hydrology is driven by climate forcing, near ground surface characteristics, and human activities, addressing a wide spectrum of environmental and water resource problems regarding both scientific-driven questions and practical engineering issues. This book collates watershed problems and solutions from around the world covering diverse climate types. These cases show complex interactions between hydrological processes and environmental conditions and scientific methods for understanding the hydrological regime and management of human activities. This book can be used as a state-of-the-art resource for academic researchers and water resource professionals, and will also appeal to students, scholars, and general readers interested in watershed models, water management, environmental management, climate change impact assessment, or ecohydrologic interactions.